Elemental and chemical composition of moringa oleifera husk extracts - Mohammed Saedi, Jami; Mani Malam, Ahmad; Olalere, Olusegun Abayomi; Mohammed, Ngabura (Universiti Malaysia Pahang, 2019)
Moringa oleifera is a well-known tropical plant with myriads medicinal and nutritional benefits. Its nutraceutical functions are due to the presence of mineral element and phytochemical components which necessitate their profiling. In this study, the elemental and chemical profiles of husk wastes from Moringa oleifera plants were elucidated using Liquid Chromatography equipped with an electrospray time-of-flight mass spectrometer (LCMS-QToF) and X-ray Fluorescence analyser. The confirmation of 493 bioactive compounds and two higher concentrations of micronutrients (calcium and potassium) indicated the potential of the Moringa oleifera extracts for medicinal and nutritional purposes. Also, the minimal presence of trace elements such as Cu, Si, Mo and Sr showed that they are non-toxic and can therefore be used as food supplement for both human and in animal feed. The result of this researchcould therefore provide lead for future investigation.